Visualized peritoneal fluid variation in adolescents and young adults with endometriosis: is there more to it? - Yousif, Abdelrahman; DePari, Mary; Vitonis, Allison F.; Harris, Holly R.; Shafrir, Amy L.; Terry, Kathryn L.; Missmer, Stacey A.; Sasamoto, Naoko (Frontiers in Reproductive Health, 2023)
Background Peritoneal fluid is a medium for endometriosis-associated biomarker discovery from which the local peritoneal environment and pathophysiologic pathways are often inferred. Therefore, we evaluated the associations between peritoneal fluid color and volume at time of endometriosis-related laparoscopic surgery with patient characteristics, endometriosis type and lesion location in adolescents and young adults with endometriosis. Methods We conducted a cross-sectional analysis among 545 patients undergoing surgery for endometriosis who enrolled in the Women's Health Study: from Adolescence to Adulthood cohort study. Patient characteristics, surgically visualized endometriosis phenotypes, and gross characteristics of peritoneal fluid were collected in compliance with World Endometriosis Research Foundation Endometriosis Phenome and Biobanking Harmonization Project (EPHect) tools. Chi-square or Fisher's exact tests were applied to test for differences across categories. Results Most of the patients were adolescents or young adults (86% age <25 years) of white race (89%), with only superficial peritoneal lesions and rASRM stage = I/II observed at surgery (both 95%). We observed variation in peritoneal fluid color across different menstrual cycle phases at time of surgery (p = 0.006). Among those who were cycling at time of surgery, endometriosis patients with red peritoneal fluid were most likely to be in the proliferative phase (49%) compared to the secretory phase (27%), while those with yellow or orange peritoneal fluid were most likely to be in the secretory phase (57% and 86% respectively). Yellow color was significantly less common in those taking combined oral contraceptives but much more common with progesterone only formulation exposure (p = 0.002). Peritoneal fluid volume did not differ by cycle phase but was more likely to be low (≤6 ml) for those exposed to hormones at time of surgery (p = 0.01). Those with acyclic pelvic pain were less likely to have red peritoneal fluid (p = 0.001) but had greater volume (p = 0.02) compared to those without. Conclusion Our findings highlight the importance of accounting for menstrual cycle phase and hormonal exposures when designing research using peritoneal fluid samples and inferring from biomarker results intended to advance our understanding of endometriosis and associated symptom pathophysiology.